Atherosclerosis-related biomarkers in women with endometriosis: The effects of dienogest and oral contraceptive therapy. (July 2020) - Maeda, Eiko; Koshiba, Akemi; Mori, Taisuke; Ito, Fumitake; Kataoka, Hisashi; Okimura, Hiroyuki; Sugahara, Takuya; Tarumi, Yosuke; Kusuki, Izumi; Khan, Khaleque N.; Kitawaki, Jo
Abstract: Objective: Chronic inflammation in endometriosis is associated with increased risk of future cardiovascular disease; however, no studies have investigated the cardiovascular risk of women who have undergone hormonal therapy for endometriosis. We investigated atherosclerosis-related biomarkers in women with and without endometriosis and the effects of dienogest (DNG) and oral contraceptive (OC) therapies. Study design: In this cross-sectional study, 109 women with endometriosis and 42 control women without endometriosis were enrolled. The endometriosis group was divided into the untreated (n = 34), DNG therapy (n = 33), and OC therapy (n = 42) groups. Lipid profile serum levels, inflammatory marker such as high-sensitivity C-reactive protein, oxidative stress markers such as oxidized low-density lipoprotein and diacron-reactive oxygen metabolites, and atherosclerosis indicators (cardio-ankle vascular index [CAVI] and ankle-brachial pressure index [ABI]) were measured. Results: The median treatment duration was 28 months in the DNG group and 32.5 months in the OC group. Triglyceride levels were higher in the OC group than in the other three groups ( P  <  0.05). Regarding markers of inflammation and oxidative stress, log high-sensitivity C-reactive protein and diacron-reactive oxygen metabolites levels were higher in the untreated group than in the control group ( P  <  0.05), and these markers were further increased in the OC group (log high-sensitivity C-reactive protein: P  <  0.05; diacron-reactive oxygen metabolites: P  <  0.01), but not in the DNG group. There was no difference in the CAVI and ABI among all groups. Spearman correlation revealed a positive correlation between duration of OC therapy and CAVI (ρ = +0.49; P = 0.002), but no correlation between the duration of DNG therapy and CAVI (ρ = –0.04; P = 0.81). Conclusions: Inflammation and oxidative stress markers are increased in women with untreated endometriosis. Treatment with OC, but not with DNG, further increases these levels. There was a positive association between the duration of OC administration and atherosclerosis risk for women with endometriosis. Our results suggest that DNG could be administered to endometriosis without the increased atherosclerosis risk and short-term OC administration for endometriosis is not harmful, however, atherosclerosis risk should be strictly observed.